Psychological Flexibility and Parenting Stress in Divorced Parents - Ali Güngör; Özlem Haskan Avcı (Uluslararası Türk Eğitim Bilimleri Dergisi)
This study aims to determine the psychological flexibility of divorced parents in predicting parenting stress and to evaluate their psychological flexibility according to their demographic characteristics. The study participants were 206 officially divorced mothers and fathers living with their children. Between June and July 2024, the data were collected using the Psychological Flexibility Scale, Parenting Stress Scale, and a demographic information form created by the researchers. The differences between the psychological flexibility levels of the participants according to their gender, income level, number of children they have, and the number of children under their custody were analyzed by t-test for independent samples, and the differences between the psychological flexibility levels according to their age, education level and the time elapsed since ANOVA analyzed the official divorce for independent samples. Multiple linear regression analysis was used to determine the extent to which participants' psychological flexibility levels predicted parenting stress. As a result of these analyses, it was found that the psychological flexibility sub-dimensions of values and acting in line with values, being in the moment, acceptance, contextual self, and defusion significantly predicted the participants' parenting stress, and these sub-dimensions explained 21% of the change in the participants' parenting stress. The findings showed that the psychological flexibility levels of male participants were higher than those of female participants, participants aged between 36-45 years were higher than those aged between 20-35 years, and participants who had been divorced for 48-60 months were higher than those who had been divorced for less than one year. No significant difference was found in the psychological flexibility levels of the participants according to the level of education and income and the number of children owned and under custody.